Managing bank risk : an introduction to broad-base credit engineering - Glantz, Morton (Amsterdam ; Boston : Academic Press, 2003)
Provides print and electronic risk-measuring tools that ensure credits are made in accordance with bank policy and regulatory requirements, giving bankers with the data necessary for judging asset quality and value. The book's two sections, "New Approaches to Fundamental Analysis" and "Credit Administration," show readers ways to assimilate new tools, such as credit derivatives, cash flow computer modeling, distress prediction and workout, interactive risk rating models, and probabilistic default screening, with well-known controls. By following the guidelines of the Basel Committee on Banking Supervision, Managing Bank Risk offers useful models, programs, and documents essential for creating a sound credit risk environment, credit granting processes, and appropriate administrative and monitoring controls.
"CD ... includes a collection of banking and risk models and related software"--P. xix.
Includes bibliographical references and index.
gau 28/01/14
Loans
Keywords: Bank management; Asset-liability management; Risk management